PENGEMBANGAN KARAKTER ANAK MELALUI FUNGSI EDUKATIF AGAMA ISLAM - Hardianto Rahman (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2012)
This study is objective to: 1) to describe the concept and character of children's development strategy, 2) to decrypt the educative function of religion in developing a child's character.The method of use in this study such as: critical methods, the method instutitif, the dialectical method and the scholastic method. This study included in the research literature. The writer tried to find the data, theories related to the issues that raised in varieties of literature or references the writer found then compared by using the methods above.The conclusion from this study show that: first, the principles of Developmentally Appropriate Practices in character development strategies carried out by instilling the basic ethical values (core ethical values) as a basis for good character. The goal is the formation of good character; second: One of the functions of religious leader in Islam is in the field of education, namely, Islam has always taught religious education and guiding all his people to always be able to highlight the attitudes and practice as well as any kind of action in accordance with religious values in everyday life. In addition, he also encourages individuals to always comply with and obey and implement the teachings and religious orders. Educational values are reflected in every teaching of Islam in order to establish good moral character of Muslims